The speeches of Frederick Douglass : a critical edition - Douglass, Frederick, 1818-1895 (Yale University Press, 2018)
A collection of twenty of Frederick Douglass's most important orations This volume brings together twenty of Frederick Douglass's most historically significant speeches on a range of issues, including slavery, abolitionism, civil rights, sectionalism, temperance, women's rights, economic development, and immigration. Douglass's oratory is accompanied by speeches that he considered influential, his thoughts on giving public lectures and the skills necessary to succeed in that endeavor, commentary by his contemporaries on his performances, and modern-day assessments of Douglass's effectiveness as a public speaker and advocate.